If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3y) = 0 (x * 3 + 3y * 3) = 0 (3x + 9y) = 0 Solving 3x + 9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 3x + 9y + -9y = 0 + -9y Combine like terms: 9y + -9y = 0 3x + 0 = 0 + -9y 3x = 0 + -9y Remove the zero: 3x = -9y Divide each side by '3'. x = -3y Simplifying x = -3y
| 5y-[2(y+1)]=7y | | 3x=15+6 | | 18x+4x+29=139 | | -0.5x-2=-12 | | -7y+4=3y-6 | | 5f+(-3)f+14= | | -8+2x=22 | | 10(15x+16)=-890 | | 5.5y=-9 | | 5x+7x+3=39 | | (1+lnx)(2-lnx)=o | | t^2+9t-162=0 | | 37x-23=273 | | 6(7-3)+7(8-6)= | | 360-(3x+4)=x | | -18=3+3u | | 360-(3x+4)=99 | | 6x^3-8=40 | | -10(s+1)=-11 | | 36=2u+12 | | -.1x^2+.1x+3=0 | | 3-f=6f+6 | | 3/4d=1/2 | | -176=-31+5x | | f(x)=2/3x-10 | | N/8=1.7 | | 17-2/3 | | 6(3s+1)=42 | | 16z^2+142=96z | | 22x-9=275 | | 3x+4=99 | | 3(2l+6)=30 |